Neurotrophic, Gene Regulation, and Cognitive Functions of Carboxypeptidase E-Neurotrophic Factor-α1 and Its Variants - Xiao, Lan; Yang, Xuyu; Loh, Y. Peng (Frontiers in Neuroscience, 2019)
Carboxypeptidase E, also known as neurotrophic factor-α1, (CPE-NFα1), was first discovered as an exopeptidase and functions to cleave C-terminal basic amino acids from prohormone intermediates to produce mature peptide hormones and neuropeptides in the endocrine and central nervous systems, respectively. CPE-NFα1 also plays a critical role in prohormone sorting and secretory vesicle transport. Recently, emerging studies have indicated that CPE-NFα1 exerts multiple non-enzymatic physiological roles in maintaining normal central nervous system function and in neurodevelopment. This includes potent neuroprotective and anti-depressant activities, as well as stem cell differentiation effects. In addition, N-terminal truncated variants of CPE-NFα1 have been identified to regulate expression of important neurodevelopmental genes. This mini-review summarizes recent advances in understanding the mechanisms underlying CPE-NFα1’s function in neuroprotection during stress and aspects of neurodevelopment.